Immediate Maternal Complications in Vacuum Vaginal Deliveries (Medical Forum Monthly, 2024)
Objective: To prove that vacuum is safe and can reduce c/section rate if patient selection is proper and conducted by trained obstetrician.Study Design: Observational retrospectivePlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Rehman Medical Institute, Peshawar KPK from July 2017 to December 2018.Materials and Methods: A total number of 59 instrumental deliveries included. All patients were closely followed throughout labour while maintaining partogram, prolong second stage was considered to be 2-3 hours for nulliparous and 1-2 hours for multiparous women as per ward protocol. Foetal distress was diagnosed either by meconium staining or non re assuring foetal heart rate tracing. Poor maternal effort was highly subjective and more associated with prolong labour.Results: There were 58 (98.30%) were vacuum and only one was forceps delivery.26 (44 %) patients were nulliparous and 33 (56%) were multi parous. Most common indication for instrumental deliveries was prolong second stage [n=29(49.1%)] followed by poor maternal effort [n=19(32.2 %)] No serious maternal complications were noticed in all 59 patients.7 (11.8%) patients went into mild to moderate post-partum haemorrhage. Five (8.4%) patients received vaginal tears. Four (6.7%) patients had perineal tears. Only one patient experienced shoulder dystocia.Conclusion: Vacuum is not associated with serious immediate maternal complications provided it is conducted by trained obstetrician and in properly selected patients.